Impact of the Internet on economic development of the member countries of the Andina Community [Incidencia del internet en el desarrollo económico de los países miembros de la Comunidad Andina] - Garcia Macias , P. (2016)
The economic development of a country is conceived from several perspectives, one of them is the technology and, within it, the Internet that is a tool that promotes the business innovation, the social inclusion through services related to education, health, etc. In this context, this document, shows an analysis of the incidence of the Internet in the economic development countries members of the Andina Community that keeps economies emerging and whose possibility of economic take-off occurs at the hands of the network and that this intensive use of this, it is considered, it can decrease the digital divides and thus develop the economic of these countries because they have a long way to go.